HUBUNGAN PEMBERIAN MP-ASI DENGAN KEJADIAN KONTIPASI PADA BAYI USIA DI BAWAH 6 BULAN DI KLINIK “PA” HAMPARAN PERAK - Yuka Oktafirnanda (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2018)
The best food for babies aged 0-6 is breast milk. Mother's Milk (ASI) is the best and most ideal source of energy with a balanced composition according to the needs of the baby during the growth period, the benefits of breastfeeding are not only felt by babies but also by mothers, the environment and even the country. The food digestive system is related to receiving food and preparing it for processing by the body. The food digestion process can occur normally and can experience interference, this is because food substances are digested by the body, so that digestive problems can occur such as constipation. Constipation is a defect that is no more frequent than every three days. In normal children, stool consistency and frequency of bowel movements can vary. Breast milk may experience defecation after each breastfeeding or only once every 7-10 days. Babies fed with formulas and older children may experience bowel movements every 2-3 days. The Purpose study was to determine the frequency distribution of MP-ASI, contipation and to know the relationship between MP-ASI and contipation. This type of research is using analytic survey research methods with Crossectional design. The samples to be studied were 30 respondents. Data were analyzed by conducting chi-square analysis test. Showed that there was a relationship between the relationship between MP-ASI and contipation, namely (p = 0.006). This study is that there is a significant relationship between the administration of MP-ASI and contipation, namely (p = 0.006).Keywords: MP-ASI, Contipation In Infant Before The Age of 6 months